Management of pesticide residues in China - Zeng-long CHEN; Feng-shou DONG; Jun XU; Xin-gang LIU; Yong-quan ZHENG (Journal of Integrative Agriculture, 2015)
This paper reviewed management of pesticide residues in China including laws and regulations, the supervision system, the standard system, and the quality and safety of agricultural products. The process of establishment and internationalization of standards for pesticide residues were also discussed. Results indicate that the progress of the management of pesticide residues has been steadily made in China. However, the following aspects which refer to updates to regulations, supervising efficiency, standard system, risk assessment, international cooperation and communication, should be further improved. China should draw lessons from international experience, and then establish its own management system, which focuses on pesticides controls by strictly following relevant laws and technical standards to ensure the quality and safety of agricultural products.